Microbiota and neurodegenerative diseases. Issue 6 (December 2017) - Marizzoni, Moira; Provasi, Stefania; Cattaneo, Annamaria; Frisoni, Giovanni B.
Abstract : Purpose of review: Despite the extensive research carried out in the past decades, the current pathophysiological notions of neurodegenerative disease as well as effective treatments to reduce their progression are largely unknown. Alterations of the human microbiota, the plethora of different microscopic organisms that our body hosts, have been linked to neurodegenerative disease risk, onset and progression. This review summarizes the current knowledge on the possible role of microbiota in neurodegenerative disorders and briefly discusses strategies to restore microbiota homeostasis. Recent findings: Preclinical evidences and human cross-sectional studies posit the gut microbiota as a key actor in the Parkinson's disease onset and progression, reporting the presence of a specific gut microbiota profile in association with the modulation of disease and symptoms. Gut microbiota alterations have been correlated with brain disease and peripheral inflammation also in Alzheimer's patients. Summary: The interaction between the microbiota and the host is promising to answer clinical questions that have so far escaped clarification with the current pathophysiological notions of health and disease. However, human longitudinal studies starting in the earlier disease phases are needed to understand the causative relation between microbiota and the hallmarks of these neurodegenerative disorders and to develop innovative treatments aimed at preventing or slowing brain damages.